2022
DOI: 10.1021/jacs.2c00260
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Regiodivergent and Enantioselective Hydrosilylation of Allenes

Abstract: A copper-catalyzed regiodivergent hydrosilylation of a wide range of simple allenes is reported. Linear and branched allylsilanes were formed by judicious choice of solvents. Furthermore, branched allylsilanes were obtained with high enantioselectivity (up to 97% enantiomeric excess) with the aid of a C2-symmetric bisphosphine ligand in the unprecedented asymmetric allene hydrosilylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 70 publications
0
26
0
2
Order By: Relevance
“…Transformation induced by the phosphine-Co complex (4 i) provided highest diastereo-and enantioselectivity (entry 9). Screening of solvents revealed that reaction proceeded with higher efficiency in non-polar solvents compared with polar solvents (entries [10][11][12][13][14]. Cobalt salts with a basic counterion promoted the reaction without erosion of stereoselectivity (entry 15), whereas transformations in the presence of Co complexes derived from cobalt halides provided no conversion of the starting materials (entries 16 and 17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation induced by the phosphine-Co complex (4 i) provided highest diastereo-and enantioselectivity (entry 9). Screening of solvents revealed that reaction proceeded with higher efficiency in non-polar solvents compared with polar solvents (entries [10][11][12][13][14]. Cobalt salts with a basic counterion promoted the reaction without erosion of stereoselectivity (entry 15), whereas transformations in the presence of Co complexes derived from cobalt halides provided no conversion of the starting materials (entries 16 and 17).…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic enantioselective hydrosilylation of unsaturated CÀ C bonds represents one of the most straightforward and atom-economical approaches for synthesis of chiral organosilanes. Although metal-catalyzed protocols for enantioselective hydrosilylation of terminal alkenes, [7b,d-k,m, n] 1,1-disubstituted alkenes, [7l] 1,3-dienes, [7s, 12] allenes, [13] cyclopropenes, [7t] vinylcyclopropanes, [7u] gemdifluoroalkenes [7v] to furnish a C-stereogenic center containing a CÀ Si bond have been revealed (Scheme 1a), more challenging construction of Si-stereogenic centers through catalytic enantioselective intermolecular hydrosilylation of alkenes and alkynes remained scarce (Scheme 1b). [7r, 8q-s] Moreover, such processes have significant limitation on the diversity of the prochiral silanes, requiring installation of specific substituents on the silanes.…”
Section: Introductionmentioning
confidence: 99%
“…These experimental results strongly support that the E -stereoselectivity of our reaction is kinetically controlled. It is known that CuH intermediates could be generated from the reaction of copper salts and silanes and CuH could add to olefins to generate organocopper intermediates 43 49 . For the reaction of allenes with CuH, both terminal and internal double bonds of 1a could participate in the hydrocupration 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to mention that copper is an earth abundant transition metal, which makes it an ideal candidate to develop transformations in sustainable chemistry. However, compared to relatively more extensively studied Ni, Co, Fe-catalyzed hydrosilylation reactions 2 , 40 42 , copper catalysis has been rarely used in hydrosilylation of unsaturated carbon carbon bonds 24 , 43 49 . Herein, we report a copper-catalyzed hydrosilylation of allenes which affords linear ( E )-allylsilanes with excellent regio- and stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy will undoubtedly represent a valuable complement for the pre-existing methods to obtain the branched allylsilanes. Therefore, on the basis of our continuous interest in the copper-catalyzed hydrosilylation reactions of unsaturated carbon–carbon bonds, , herein we report the successful copper-catalyzed Markovnikov 3,4-hydrosilylation reaction of 2-substituted 1,3-dienes with trihydrosilanes to form the branched allylsilanes in good yields and with high regioselectivities (Scheme ), which are difficult to obtain by other means.…”
mentioning
confidence: 99%